Prison Leave in Italy: Legislation and Practical Application Is the Italian Regulation on Prison Leave Ensuring the Constitutional Purpose of Punishment? - Talini, Silvia (European journal on criminal policy and research, 2020)
This paper provides a description of the prison leave regulation in the Italian criminal system in order to bring out critical points and questionable compatibility with the Italian Constitution. The work starts with an analysis of the principles of rehabilitation and the prohibition of inhuman treatments which stem from the Italian Constitution (Article 27, third paragraph) and the Prison Act (Law no. 354/1975). Particularly, Art. 30 of the Prison Act allows prison leave only for woeful events occurring in the life of the detainee. In addition, “bonus leave”—introduced by further provision in Law no. 663/1986—can be granted in order to foster family ties and cultural or work interests, but only to convicts who have maintained good behaviour while imprisoned and are not labelled as “socially dangerous”. Starting from a study of statutory law and its practical application, the paper analyses the main trends in court rulings and the recent Italian prison system reform, entered into force in October 2018.